High-throughput, detailed, cell-specific neuroanatomy of dendritic spines using microinjection and confocal microscopy - Dumitriu, Dani; Rodriguez, Alfredo; Morrison, John H (Nature protocols, 2011)
Morphological features such as size, shape and density of dendritic spines have been shown to reflect important synaptic functional attributes and potential for plasticity. Here we describe in detail a protocol for obtaining detailed morphometric analysis of spines using microinjection of fluorescent dyes, high-resolution confocal microscopy, deconvolution and image analysis with NeuronStudio. Recent technical advancements include better preservation of tissue, resulting in prolonged ability to microinject, and algorithmic improvements that compensate for the residual z -smear inherent in all optical imaging. Confocal imaging parameters were probed systematically to identify both optimal resolution and the highest efficiency. When combined, our methods yield size and density measurements comparable to serial section transmission electron microscopy in a fraction of the time. An experiment containing three experimental groups with eight subjects each can take as little as 1 month if optimized for speed, or approximately 4–5 months if the highest resolution and morphometric detail is sought.